Elevated Aspartate and Alanine Aminotransferase Levels and Natural Death among Patients with Methamphetamine Dependence - Kuo, Chian-Jue; Tsai, Shang-Ying; Liao, Ya-Tang; Conwell, Yeates; Lee, Wen-Chung; Huang, Ming-Chyi; Lin, Shih-Ku; Chen, Chiao-Chicy; Chen, Wei J. (PLOS ONE, 2012)
Background Methamphetamine is one of the fastest growing illicit drugs worldwide, causing multiple organ damage and excessive natural deaths. The authors aimed to identify potential laboratory indices and clinical characteristics associated with natural death through a two-phase study. Methods Methamphetamine-dependent patients (n = 1,254) admitted to a psychiatric center in Taiwan between 1990 and 2007 were linked with a national mortality database for causes of death. Forty-eight subjects died of natural causes, and were defined as the case subjects. A time-efficient sex- and age-matched nested case-control study derived from the cohort was conducted first to explore the potential factors associated with natural death through a time-consuming standardized review of medical records. Then the identified potential factors were evaluated in the whole cohort to validate the findings. Results In phase I, several potential factors associated with natural death were identified, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), comorbid alcohol use disorder, and the prescription of antipsychotic drugs. In phase II, these factors were confirmed in the whole cohort using survival analysis. For the characteristics at the latest hospital admission, Cox proportional hazards models showed that the adjusted hazard ratios for natural death were 6.75 (p<0.001) in the group with markedly elevated AST (>80 U/L) and 2.66 (p<0.05) in the group with mildly elevated AST (40–80 U/L), with reference to the control group (<40 U/L). As for ALT, the adjusted hazard ratios were 5.41 (p<0.001), and 1.44 (p>0.05). Comorbid alcohol use disorder was associated with an increased risk of natural death, whereas administration of antipsychotic drugs was not associated with lowered risk. Conclusions This study highlights the necessity of intensive follow-up for those with elevated AST and ALT levels and comorbid alcohol use disorder for preventing excessive natural deaths.